2020
DOI: 10.14716/ijtech.v11i5.4323
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric Detection of Dopamine based on a Graphene Oxide/PEDOT:PSS Composite Electrode

Abstract: Dopamine (DA) is a hormone and a neurotransmitter that plays many important roles within the brain and body. It is an organic compound in the catecholamines and phenethylamines groups. A considerable effort has been made since its discovery, and numerous techniques for DA detection have been developed. Graphene and its derivatives have great potential for the development of sensors and biosensors. Since it has excellent characteristics, such as good conductivity and a large surface area, a graphene-based biose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The presence of a new peak at the position of 2θ (about ~28.0°) is a graphitic phase peak (Poorali and Bagheri-Mohagheghi, 2017). Furthermore, it is also shown that there are no peaks at positions 2θ of 10°~12°, which indicates there is no formation of graphene oxide (GO) or reduced graphene oxide (rGO) (Kusrini et al, 2019;Hardi and Rahman, 2020). These results indicate that the produced graphene in this study did not undergo any oxidations.…”
Section: Xrd Analysismentioning
confidence: 52%
“…The presence of a new peak at the position of 2θ (about ~28.0°) is a graphitic phase peak (Poorali and Bagheri-Mohagheghi, 2017). Furthermore, it is also shown that there are no peaks at positions 2θ of 10°~12°, which indicates there is no formation of graphene oxide (GO) or reduced graphene oxide (rGO) (Kusrini et al, 2019;Hardi and Rahman, 2020). These results indicate that the produced graphene in this study did not undergo any oxidations.…”
Section: Xrd Analysismentioning
confidence: 52%
“…The measurement shows that those various dopamine concentrations were clearly distinguishable. This could be the best candidate for a non-enzymatic dopamine biosensor (Hardi et al, 2020;Rahman et al, 2016).…”
Section: Dopamine Detection Using In Situ Measurementmentioning
confidence: 99%
“…Previous studies showed that multi-walled carbon nanotube (MWCNT) scaffold had good characteristics for adhesion, proliferation, and osteogenesis differentiation (Xu et al, 2019). Meanwhile, graphene-based materials and the derivatives, such as graphene oxide (GO) and reduced graphene oxide (rGO), which possess high surface area and electrical conductivity (Hardi and Rahman, 2020), have also been investigated to enhance cell attachment and differentiation (Sanati et al, 2022).…”
Section: Introductionmentioning
confidence: 99%